2005
DOI: 10.1007/s10750-004-6953-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton distribution in the Caspian Sea during March 2001

Abstract: Phytoplankton abundance, biomass and species composition of the Caspian Sea were evaluated by using samples collected from the Iranian (southern Caspian Sea) and southern Kazakhstan (eastern Caspian Sea) surface waters in March 2001. A total of 45 taxa were found in the samples (20 diatoms, 17 dinoflagellates and 8 others). Abundance and biomass of diatoms were high at the eastern stations, while dinoflagellates were dominant in terms of both biomass and abundance in the southern region. Average abundance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
6
16
1
Order By: Relevance
“…Kideys et al (2008) also revealed that after 1999 chlorophyll a levels gradually increased and reached extremely high levels of 9.00 μg L -1 in August 2001 using satellite imagery. In addition, the average chlorophyll a value for the Caspian Sea was calculated as 1.63 μg L -1 in March 1998 (Kideys et al 2005) and as 2.62 μg L -1 in 2001 by Kideys et al (2005). In our study, the annual average chlorophyll a value during the sampling period was calculated by far higher (9.26 ± 3.54 μg L -1 ) than those reported in previous studies.…”
Section: Quantitative Phytoplankton Compositioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Kideys et al (2008) also revealed that after 1999 chlorophyll a levels gradually increased and reached extremely high levels of 9.00 μg L -1 in August 2001 using satellite imagery. In addition, the average chlorophyll a value for the Caspian Sea was calculated as 1.63 μg L -1 in March 1998 (Kideys et al 2005) and as 2.62 μg L -1 in 2001 by Kideys et al (2005). In our study, the annual average chlorophyll a value during the sampling period was calculated by far higher (9.26 ± 3.54 μg L -1 ) than those reported in previous studies.…”
Section: Quantitative Phytoplankton Compositioncontrasting
confidence: 58%
“…Similarly, during the present study, temperature variation in the surface waters varied between 6.80°C (in winter) and 29.8°C (in summer). Kideys et al (2005) reported that temperature was an important factor in the fluctuations of phytoplankton composition in the Caspian Sea. They showed that diatoms were dominant in the colder waters of the eastern Caspian Sea, while dinoflagellates were prevalent in the warm waters of the southern Caspian Sea.…”
Section: Quantitative Phytoplankton Compositionmentioning
confidence: 99%
“…Surveys of the surface water of the CS have recorded about 440 phytoplanktonic species, the northern basin containing the greatest diversity (Kasymov and Rogers, 1996). Surveys in the 1960s and 1970s showed that dinoflagellates composed 9% of the phytoplankton population, whereas a recent survey (2001) indicates that almost half of the population consist of dinoflagellates (Kideys et al, 2005). However, this survey, before springtime, does not indicate any occurrence of Gonyaulax species.…”
Section: Hydrobiological Settingmentioning
confidence: 60%
“…In addition, the species number was found to decrease from the north (414 species) to the middle (225 species) and the southern area (71 species) mainly due to the disappearance of fresh water forms towards the south (Dumont, 1998). Recently, Kideys et al (2005; reported there was a significant increase in phytoplankton abundance and noxious visibility in the Caspian Sea. Moreover, Nasrollahzadeh et al (2008a) and Bagheri et al (2010) observed an increase in phytoplankton abundance in 2001-2002 and 2005 as compared to previous years.…”
Section: Inrtoductionmentioning
confidence: 98%